Controle das vibrações não lineares do sistema acoplado torre eólica-pás - Martins, Yuri Luiz Dias (2021)
Slender structures, such as wind towers, are very flexible and can undergo large displacements when subjected to external loads, considering the occurrence of coupling between tower and blades. An important way to reduce these excessive vibrations is to apply structural control. In this work, the structural control of a coupled wind tower–blade system subjected to external lateral loads and rotating blade is studied. To model the tower and blade, the nonlinear Euler-Bernoulli beam theory and the linear Euler-Bernoulli beam, respectively, are considered, and the structural control device considered is an inverted pendulum tuned mass damper, located at the top of the tower. The Rayleigh-Ritz method, together with Hamilton principle, is applied to obtain a set of nonlinear ordinary differential equations of motion which are, in turn, solved by the Runge-Kutta method. First, the dynamic instability is studied from the variation of the natural frequency with respect to the speed of rotation of the blade, where it is possible to observe the phenomenon of veering. In addition, the time response in resonance situations is obtained, as well as the optimum parameters of the mass damper tuned as an inverted pendulum. Next, a nonlinear dynamic analysis is performed to evaluate the influence of the tuned mass damper in the nonlinear regime, by obtaining the resonance curves, Poincaré sections and basins of attraction. The results demonstrate a good performance of the structural control in the dynamic behavior of the system.